(untitled) (Conference Zone, 2022)
These studies are devoted to the study of the operational properties of new varieties of cotton. A comparative analysis of new varieties of fine-staple cotton fiber Porlok-1 (P-1), Porlok-2 (P-2) with zoned fiber grade S-6524 was carried out. New grades of cotton fiber have better indicators of maturity, have higher values of strength, length and index of uniformity along the length. An assessment of the spinning and technological properties of the yarn showed that the yarn produced from the fiber of the experimental P-1, P2 and control selection corresponded to the level of the I-grade, and C-6524 of the obtained data, the indicators of the II-grade. Based on the results of the data obtained, it was established that in the process of creating a textile material, the structure of fibrous raw materials created by nature and in the processing processes contributes to the formation of quality indicators, as well as operational and consumer properties.